2017
DOI: 10.1158/1078-0432.ccr-17-0231
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Cell–Free DNA Copy Number Instability Predicts Therapeutic Response to Immunotherapy

Abstract: Purpose: Chromosomal instability is a fundamental property of cancer, which can be quantified by next-generation sequencing (NGS) from plasma/serum-derived cell-free DNA (cfDNA). We hypothesized that cfDNA could be used as a real-time surrogate for imaging analysis of disease status as a function of response to immunotherapy and as a more reliable tool than tumor biomarkers.Experimental Design: Plasma cfDNA sequences from 56 patients with diverse advanced cancers were prospectively collected and analyzed in a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(105 citation statements)
references
References 31 publications
2
96
0
4
Order By: Relevance
“…Whilst some lung cancer studies have recently investigated LBs, currently none have truly examined their use for histological subtyping [25,[30][31][32][33][34]. To evaluate the adopted modeling approach, we therefore compared ours to other published tissue-based alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst some lung cancer studies have recently investigated LBs, currently none have truly examined their use for histological subtyping [25,[30][31][32][33][34]. To evaluate the adopted modeling approach, we therefore compared ours to other published tissue-based alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Weiss et al recently reported that chromosomal instability as reflected by copy number variation in cell-free DNA correlated with response to immunotherapy, consistent with our observations with number of alterations. (25). Future studies should also compare cfDNA and tissue NGS mutational burden, preferably with biopsies and blood tests obtained on the same day.…”
Section: Discussionmentioning
confidence: 99%
“…CNAs are a major contributing factor that modulate tumorigenesis and drug responses . Two PDX models of non‐small cell lung carcinoma (NSCLC) showed higher copy number signals compared to parental tumors .…”
Section: Differences In Molecular Characteristics Among Pdx Modelsmentioning
confidence: 99%